From On-Premises to Cloud: Trends and Best Practices in Cloud Migration - Muhammad Adam Zaidan; Mochamad Teguh Kurniawan (CV. ULIL ALBAB CORP, 2024)
In the modern era of information technology, it has been a rising trend in implementing cloud-based services in businesses and organizations. The main goal of this paper is to provide an overview of the current state and research on cloud services and migration, focusing on the strategies, trends, and best practices both old and newly surfacing trends. Through a comprehensive analysis of several articles, journals, and case studies, this literature review aims to be a rough guideline for cloud migration, explaining the benefits such as business continuity, scalability, and cost effectiveness. This paper also aims to explore several migration tactics, including lift-and-shift, refactoring, and replatforming, and offers a critical assessment of their benefits and drawbacks. The review also discusses typical obstacles encountered in cloud migration, such as organizational resistance, data integration problems, and security worries. By investigating real-world instances and acquired knowledge, this paper offers practical insights and recommendations for organizations that are planning or undergoing cloud migration through real-world findings and lessons learned. The results highlight the importance of crucial planning, effective change management, and ongoing performance optimization in achieving successful cloud transitions. This literature review highlights the need for continuous innovation and adaptation in the quickly changing cloud landscape by consolidating current knowledge and outlining future research.